Utilization of peanut milk in vegetable toned milk - De Castro, Julia G. II (1978)
A temperature range of 28°C to 40°C was found to be applicable for extracting peanut milk from the peanuts. Subjecting the peanut milk to steam bubbles for 15 minutes lessened the undesirable peanut odor and flavor. A prolonged process of steam bubbling, however, brought destruction to peanut protein. A peanut milk to cow's milk combination of 25 to 75 by volume was the most acceptable combination for this vegetable toned milk. Test performed on this product gave 7.8% soluble solids, pH 6.4 and a protein content of 3.54%.